2016
DOI: 10.1177/0271678x16671964
|View full text |Cite
|
Sign up to set email alerts
|

Stroke-induced immunodepression and dysphagia independently predict stroke-associated pneumonia – The PREDICT study

Abstract: Stroke-associated pneumonia is a frequent complication after stroke associated with poor outcome. Dysphagia is a known risk factor for stroke-associated pneumonia but accumulating evidence suggests that stroke induces an immunodepressive state increasing susceptibility for stroke-associated pneumonia. We aimed to confirm that stroke-induced immunodepression syndrome is associated with stroke-associated pneumonia independently from dysphagia by investigating the predictive properties of monocytic HLA-DR express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
193
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(209 citation statements)
references
References 42 publications
6
193
0
10
Order By: Relevance
“…Accordingly, we observed a clearly higher pneumonia proportion in dysphagic patients compared to those with normal swallowing function. This is in line with the range of 13–33% reported for dysphagic stroke patients in the literature [1, 26, 28]. The vast majority of our patients were treated on SUs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Accordingly, we observed a clearly higher pneumonia proportion in dysphagic patients compared to those with normal swallowing function. This is in line with the range of 13–33% reported for dysphagic stroke patients in the literature [1, 26, 28]. The vast majority of our patients were treated on SUs.…”
Section: Discussionsupporting
confidence: 90%
“…Dysphagia is known to be an independent predictor of post-stroke pneumonia, in addition to poor oral health and stroke-induced immune suppression [26-28]. Accordingly, we observed a clearly higher pneumonia proportion in dysphagic patients compared to those with normal swallowing function.…”
Section: Discussionsupporting
confidence: 47%
“…27 Clinically, reduction of HLA-DR expression in monocytes is a prognostic marker of strokeinduced immune suppression and SAP. 2,28,29 Interestingly, we found that ischemic stroke increases the expression of the monocyte chemoattractant CCL2 in the lungs, yet monocyte infiltration into the lungs was not observed. Conversely, following ischemic stroke, we observed a massive infiltration of monocytes into the brain, which may account for temporal peripheral immune exhaustion following ischemic stroke.…”
Section: Discussionmentioning
confidence: 69%
“…Finally, accumulating evidence suggests that a stroke induces an immunodepressive state increasing susceptibility for stroke‐associated pneumonia (SAP). Although the FBAS reliably estimates aspiration risk in the very acute phase of stroke management, dysphagia remains an important risk factor for SAP and should be formally evaluated after initial stroke work‐up in order to make informed physiology‐based treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that hospitals that adhere to formal screening protocols can significantly lower their rates of pneumonia 49 and that acute stroke patients who are not screened early for swallowing risk present with a higher risk of developing pulmonary complications. 2,14,50 Finally, accumulating evidence 51,52 suggests that a stroke induces an immunodepressive state increasing susceptibility for stroke-asso-…”
Section: Discussionmentioning
confidence: 99%